2017
DOI: 10.5812/ircmj.44566
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Mindfulness-Integrated Cognitive Behavior Therapy on Depression, Anxiety, and Stress in Females with Multiple Sclerosis: A Single Blind Randomized Controlled Trial

Abstract: Background: Previous studies have shown the effectiveness of cognitive behavior therapy in improvement of psychological symptoms such as depression, anxiety, and stress. Recent studies suggest that mindfulness-based interventions (MBI) are effective in reducing these psychological symptoms in chronic diseases. The present study was the first study to examine the effects of mindfulness-integrated cognitive behavior therapy (MiCBT) on common comorbid psychological symptoms in patients with multiple sclerosis (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twelve RCTs were identified as eligible for inclusion in the systematic review. [21][22][23][24][25][26][27][28][29][30][31][32] However, only eight studies reported endpoint data that could be included in the meta-analysis. 21-24 28-30 32 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The largest overall effects were reported for MiCBT, 23 SMD 0.80 (0.48-1.12), I 2 =0%, but this was a pre-post-RCT (n=56), vs usual care. Overall effects for MBCT vs usual care came from a small study 28 (n=40), where SMD was 0.78 (0.45, 1.11), I 2 =0%.…”
Section: Outcomes By Intervention Typementioning
confidence: 87%
See 2 more Smart Citations
“…Prenatal education, as the most common psychological intervention for pregnant women in China, cannot actively target mental health, for example, by reducing depressive and anxious symptoms . Numerous studies have examined the effectiveness of psychological intervention programs, including cognitive behavioral therapy, interpersonal psychotherapy, and mindfulness interventions . In particular, the mindfulness‐based interventions have shown promise for treating or preventing diverse psychological problems, as well as for relieving pain and improving well‐being .…”
Section: Introductionmentioning
confidence: 99%